2017
DOI: 10.1123/jab.2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Shoulder Joint Position Sense Mainly Come from the Glenohumeral Joint

Abstract: While synchronous movement of glenohumeral and scapulothoracic joints has been emphasized in previous kinematics studies, most investigations of shoulder joint position sense have treated the shoulder complex as a single joint. The purposes of this study were to investigate the joint position sense errors of the humerothoracic, glenohumeral and scapulothoracic joints at different elevation angles and to examine whether the errors of the glenohumeral and scapulothoracic joints contribute to the errors of the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…28 Poor balance, measured as increased sway, has been identified in adults with GJH, 31 and a recent study found increased sway to be a predictor of injuries in a general population of children aged 9 to 15 years. 27 However, adult elite-level dancers have shown superior balance ability compared to the general population, possibly because the elite-level training leads to a protective effect against falling, even in dancers with GJH.…”
mentioning
confidence: 99%
“…28 Poor balance, measured as increased sway, has been identified in adults with GJH, 31 and a recent study found increased sway to be a predictor of injuries in a general population of children aged 9 to 15 years. 27 However, adult elite-level dancers have shown superior balance ability compared to the general population, possibly because the elite-level training leads to a protective effect against falling, even in dancers with GJH.…”
mentioning
confidence: 99%
“…It is thought that participation of the athletes without a shoulder injury, a stronger association of scapular asymmetry with scapular asymmetry scapulothoracic joint than the glenohumeral joint might be the reason for this result. It is suggested that the sense of proprioception of the scapulothoracic joint should be evaluated as the sense of proprioception of the glenohumeral joint, in the presence of the scapular asymmetry [26].…”
Section: Discussionmentioning
confidence: 99%
“…Les muscles seraient alors simplement les effecteurs de la proprioception et non du mouvement. Cependant, il semble que ce recours ne soit pas suffisant car la proprioception est moins efficace lors de la mobilisation passive plutôt qu'active, les muscles en étant effecteurs lorsqu'ils sont contractés (11,20).…”
Section: Discussionunclassified
“…Actuellement, les tests développés s'attachent à évaluer la SPA et nécessitent souvent une instrumentation spécifique, souvent coûteuse et parfois difficile à mettre en oeuvre (9,10). Tester la SPA en mobilité active en donne un reflet plus précis de par la contraction musculaire produisant des signaux afférents, participant à la stabilité et présente dans les gestes de la vie quotidienne (11). En utilisant cette méthode de mesure, l'objectif primaire de cette étude était d'isoler les facteurs pouvant influencer l'évaluation de la SPA au niveau de la ceinture scapulaire chez des sujets sains.…”
Section: Introductionunclassified